A gendered assessment of the brain drain - Frédéric Docquier; B. Lindsay Lowell; Abdeslam Marfouk (Institute for the Study of Labor (IZA), 2007)
This paper updates and extends the Docquier-Marfouk data set on international migration by educational attainment. We use new sources, homogenize definitions of what a migrant is, and compute gender-disaggregated indicators of the brain drain. Emigration stocks and rates are provided by level of schooling and gender for 195 source countries in 1990 and 2000. Our data set can be used to capture the recent trend in women's brain drain and to analyze its causes and consequences for developing countries. We show that women represent an increasing share of the OECD immigration stock and exhibit relatively higher rates of brain drain than men. The gender gap in skilled migration is strongly correlated with the gender gap in educational attainment at origin. Equating women's and men's access to education would probably reduce gender differences in the brain drain.
Keywords: F22; 330; Brain drain; gender; human capital; migration; Internationale Wanderung; Brain Drain; Geschlecht; Bildungsniveau; Welt